Homer 1 genotype AA variant relates to congenital splay leg syndrome in piglets by repressing Pax7 in myogenic progenitors - Schumacher, Toni; Reyer, Henry; Maak, Steffen; Röntgen, Monika (Frontiers in Veterinary Science, 2023)
Porcine congenital splay leg syndrome (PCS) is a major birth defect in piglets resulting in lameness and high mortality rates. The multifactorial pathogenesis of PSC is not well understood but includes a polygenic inheritance. Here, in addition to morphological investigations, we characterized the expression of myogenic genes and functional (proliferation, differentiation) properties of myogenic precursor / satellite cells (SATC) in one day-old PCS piglets, non-affected littermates (LC) and piglets from PCS-free healthy litters (HC). In addition, PCS-phenotypes were related to the SNP Homer1_rs325197091 within the Homer1 locus which has been identified as a potential hereditary cause of PCS. Samples from musculus semitendinosus (ST) of PCS piglets had a higher proportion of type II fibers reflecting myofiber immaturity. In addition, myofiber atrophy, a lower number of myonuclei per fiber (ST) and a higher apoptotic activity (in ST and longissimus dorsi muscle; LD) were found in the PCS group. A higher proportion of cycling committed myoblasts (Pax7+/Ki67+ cells) occurred in samples from PCS affected piglets and on the other hand, the mRNA expression of genes involved in differentiation (muscle differentiation 1; MyoD, myogenin; MyoG) was repressed compared with HC. Cultured SATC from PCS-affected animals showed a temporal shift in peak expression of Pax7, MyoD and MyoG towards day 3 and 4 of their 7-day differentiation regime. In vitro experiments with isolated SATC confirmed the lower differentiation potential and the delayed progression of the myogenic processes in cells from piglets with PCS phenotype. In addition, Pax7 and desmin were differently expressed in Homer1_rs325197091 genotype variants (GG, GA, AA). Both genes showed the lowest expression in the homozygous AA-variant, which most frequently was found in PCS-affected animals. The homozygous AA-variant was also associated with lower expression of the truncated Homer1-subtype 205. Thus, we hypothesize that in PCS, the balance between Homer1 proteins and thereby its signaling functions are changed in a way detrimental to the myogenic differentiation program. Our results demonstrated direct negative effects of the Homer1 AA genotype on Pax7 expression, but the exact mode of action still needs to be elucidated.